About some features of forecasting masstransport processes in saturated - unsaturated media - Telyma, S.; Voloshkina, O. (My University, 2018)
The general methodic of forecasting the flow and moisture-salt transfer processes in saturated-unsaturated media on the base of the methods of mathematic modeling for case of the arbitrary vertical domains is proposed.The practical example of the solution the migration problem of pollutions at filtration from the irrigated channel to reservoir is demonstrated.
Keywords: forecasting; migration; pollution; filtration; moisture-salt transfer; modeling; saturated-unsaturated media